Incidence and Risk Factors of Cisplatin-Induced Acute Kidney Injury in Patients Undergoing Concurrent Chemoradiotherapy: A Retrospective Study - Rizal, Kushal; Rattan, Rajit; Thakur, Alok; Gautam, Akriti (Medical Journal of Eastern Nepal, 2025)
Background: Cisplatin is a fundamental chemotherapeutic agent for solid tumors; however, its use is constrained by dose-dependent nephrotoxicity, frequently presenting as acute kidney injury (AKI). Data regarding the incidence and risk factors of acute kidney injury (AKI) in resource-limited settings such as Nepal are limited, highlighting the need for region-specific insights to enhance therapeutic strategies. This retrospective study sought to assess the incidence of cisplatin-induced acute kidney injury (AKI) and to identify associated risk factors among patients receiving weekly cisplatin in conjunction with radiotherapy at a tertiary care center in Nepal. Methods: We analyzed 92 patients treated between 2022 and 2024, aged ≥18 years, with solid tumors. Patients received weekly cisplatin (approximately 40 mg/m²) alongside radiotherapy. AKI was defined using KDIGO criteria. Data on demographics, cancer characteristics, treatment parameters, and comorbidities were extracted from electronic medical records. Univariate and multivariate logistic regression analyses identified AKI predictors. Results: AKI occurred in 30 patients (32.6 percent), with 25.0 percent stage 1, 6.5 percent stage 2, and 1.1 percent stage 3; none required renal replacement therapy. Mean age was 54.8 years (SD 13.3), with 60.9 percent male. Head and neck cancers predominated (58.7 percent). Multivariate analysis identified older age (OR 1.05 per year, 95% CI 1.01–1.09, p=0.009) as a significant risk factor and higher cumulative cisplatin dose (OR 1.09 per 10 mg/m², 95% CI 1.00–1.19, p=0.06) as borderline significant. Hypertension showed no significant association (p=0.29). Conclusion: Approximately one-third of patients developed AKI, primarily mild, with older age and higher cisplatin doses as key risk factors. These findings underscore the need for vigilant renal monitoring in elderly patients and those receiving prolonged cisplatin therapy, informing strategies to enhance treatment safety in Nepal.